Strength taining for edurance runners - Beattie, K. (Concurrent aerobic and strength training. Scientific basics and practical applications, 2019)
Exercise economy, VO2max and sprinting ability play a vital role in elite distance running performance. Research has shown that the neuromuscular adaptations from strength training can improve these key performance indicators. Therefore, the purpose of this chapter is to discuss the importance of prescribing strength (maximal-, explosive- and reactive-strength) and speed training (technical drills and maximum-velocity sprinting) for long-term neuromuscular development. Abstract from author